The intertwined nature of socio-emotional interaction and contributions to the regulation of learning in collaborative groups - Ahola, Sara; Järvenoja, Hanna; Törmänen, Tiina; Malmberg, Jonna (International journal of educational research, 2025)
•Contributions to regulation are associated with collaborative groups’ affective states.•Regulating tasks may not be conducive to positive socio-emotional interactions.•Neutral affective states with low physiological activation can invite regulation.•Negative affective states with divergent activation may indicate a need for support. This study aims to investigate the intertwinement of group members’ regulation of learning and their socio-emotional interactions during groups’ engagement in collaborative science tasks. Specifically, the study first explores group members’ contributions to regulation that occurs alongside their socio-emotional interactions; the study then examines how different contributions are associated with the simultaneous affective states of the groups. The study involved 18 groups of three participants from a 7th grade science class who were engaged in authentic collaborative group work during a seven-week physics course. The research employed a multi-faceted approach, utilising 360-degree cameras to record collaborative sessions and Shimmer 3 GSR+ sensors to measure electrodermal activity (EDA). The analysis encompassed three key steps: a qualitative video analysis to detect socio-emotional interactions and the group-level regulation of learning between the group members, a combined analysis of affective states through a qualitative video analysis of emotional expressions and EDA data, and a statistical analysis employing a two-step cluster analysis and chi-square test to explore group members’ contributions to the regulation of learning along with the groups’ affective states. The findings revealed significant associations between affective states and contributions to the regulation of learning. Qualitative examples further illustrated these findings, which occurred in an authentic science class setting. The results are consistent with prior research emphasising the role of socio-emotional factors in the regulation of learning within collaborative learning contexts. The study contributes to the theoretical understanding of how groups with different affective states might engage in the regulation of learning to overcome challenging collaborative learning situations.